Self-Compassion, Self-Acceptance, and Subjective Well-Being in Adolescents Who Have Experienced Being Motherless Since Childhood - Irene Cecilia Siwalette; Arthur Huwae (Kuras Institute, 2025)
A mother plays a significant role and responsibility in her child's life, as her attention and affection facilitate many aspects of the child's development. The loss of a mother's role can lead to sorrow that results in disappointment and frustration for children entering their teenage years, which can if held for a long time, affect their overall life satisfaction. To help adolescents avoid negative evaluations regarding the absence of a mother’s role, it is necessary for them to better understand themselves through the application of self-compassion and unconditional acceptance of themselves. This study aims to determine the predictor of self-compassion and self-acceptance together on the subjective well-being of adolescents who have experienced motherlessness since childhood. The research method used is quantitative with a multiple regression analysis design. A total of 203 adolescents who have experienced being motherless since childhood were recruited as participants using the purposive sampling technique. The research measurement used the Self-Compassion Scale (SCS) for the self-compassion variable, the Unconditional Self-Acceptance Questionnaire (USAQ) for the self-acceptance variable, and the Positive and Negative Affect Schedule (PANAS) paired with the Satisfaction with Life Scale (SWLS) for the subjective well-being variable. The research results show that the major hypothesis is accepted (F = 29.980 and sig. = 0.000), which is that self-compassion and self-acceptance have a predictor on subjective well-being in adolescents who have experienced motherlessness since childhood. Minor hypothesis 1 is accepted (r = 0.465 and sig. = 0.000), which states that self-compassion predictor subjective well-being in adolescents who have experienced motherlessness since childhood, while minor hypothesis 2 is rejected (r = 0.042 and sig. = 0.528), indicating that self-acceptance does not predictor subjective well-being in adolescents who have experienced motherlessness since childhood. This indicates that the state of subjective well-being in adolescents who have lost the role of a mother since childhood can be influenced by the application of love and unconditional acceptance towards oneself. However, another finding in this study indicates that only self-compassion has a direct predictor, while self-acceptance has no direct predictor on the subjective well-being of adolescents who have experienced motherlessness since childhood.